Thioredoxin/Txnip: Redoxisome, as a Redox Switch for the Pathogenesis of Diseases - Yoshihara, Eiji; Masaki, So; Matsuo, Yoshiyuki; Chen, Zhe; Tian, Hai; Yodoi, Junji (Frontiers in Immunology, 2014)
During the past few decades, it has been widely recognized that reducing-oxidizing (Redox) responses occurring at the intra- and extra-cellular levels are one of most important biological phenomena and dysregulated redox responses are involved in the initiation and progression of multiple diseases. Thioredoxin 1 (Trx1) and Thioredoxin 2 (Trx2), mainly located in the cytoplasm and mitochondria, respectively, are ubiquitously expressed in variety of cells and control cellular reactive oxygen species (ROS) by reducing the disulfides into thiol groups. Thioredoxin interacting protein (Txnip/TBP-2/VDUP1) directly binds to Trx1 & Trx2 (Trx) and inhibit the reducing activity of Trx through their disulfide exchange. Recent studies have revealed that Trx1 and Txnip are involved in some critical redox-dependent signal pathways including NLRP3 inflammasome activation in a redox-dependent manner. Therefore, Trx/Txnip, a redox-sensitive signaling complex is a regulator of cellular redox status and has emerged as a key component in the link between redox-regulation and the pathogenesis of diseases. Here, we review the novel functional concept of the redox-related protein complex, named “Redoxisome”, consisting of Trx/Txnip, as a critical regulator for intra- and extra-cellular redox signaling, involved in the pathogenesis of various diseases such as cancer, autoimmune disease, and diabetes.